ANALISIS TINGKAT PENDAPATAN MELALUI BIAYA PROMOSI PADA HOTEL FIDUCIA SERPONG KOTA TENGERANG SELATAN PROVINSI BANTEN - I Nyoman Marayasa (Jurnal Ekonomi Efektif, 2018)
This study aims to find out the promotion cost incurred by the Hotel Fiducia Serpong, to determine the income level of Hotel Fiducia Serpong, and to determine the effect of promotion costs on income at Hotel Fiducia Serpong.The research method used in this research is quantitative assosiatif. Methods of collection by conducting interviews, observation, documentation and literature study. The method of analysis used is simple regression test, correlation test, test of determination, and hypothesis test (t test). the data is then processed using the Statitstical Social Science Program (SPSS) version 19.00.The results of this study show that the cost of promotion issued Hotel Fiducia Serpong fluctuate. The income level of Hotel Fiducia Serpong has fluctuated. There is a very strong and significant positive influence between the cost of promotion to the income of Hotel Fiducia Serpong. It can be seen from simple regression coefficient value Y = 1.270 + 29.143X, correlation coefficient r = 0,999, coefficient determination value R = 99,9%, and t value> t table value (21,811> 6,314). Keywords:Promotion Cost, Revenue.